2019
DOI: 10.1016/j.ijhm.2019.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Why and when witnessing uncivil behavior leads observers to punish frontline employees and leave the firm

Abstract: The present studies examined observer responses to failed recoveries following a service failure in a restaurant setting. Study 1 demonstrated that, relative to a neutral response, a negative server response increased desire for revenge and negative firm attitudes, which reduce tipping and return intentions, but revealed no benefits of a positive server response. Study 2 highlighted the full buffering effect of management apology on firm-related outcomes (attitudes, return intentions) which did not extend to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…Negative emotions, in turn, motivate individuals to assess the situation (e.g., its implications for their well-being) and respond in a way to address it (Lazarus & Folkman, 1984) often resulting in job strains (Spector & Goh, 2001), which are negative reactions to a work stressor and can manifest as psychological (e.g., negative work attitudes) or behavioral (e.g., counter-productive behaviors) (Pindek et al, 2019). Particularly for industries impacted by work events, this process can lead employees to develop negative attitudes and behaviors toward their industry, such as industry turnover intentions, defined as an employee's willingness to leave an industry (Tongchaiprasit, & Ariyabuddhiphongs, 2016) and industry negative word-of-mouth, defined as the communication of personal experiences with an industry (Karabas, Joireman, & Kim, 2019). In other words, as a way to deal with the stress and negative emotions, employees might direct their emotions and behaviors toward leaving or staying in their industry.…”
Section: Conceptual Model and Hypotheses Developmentmentioning
confidence: 99%
“…Negative emotions, in turn, motivate individuals to assess the situation (e.g., its implications for their well-being) and respond in a way to address it (Lazarus & Folkman, 1984) often resulting in job strains (Spector & Goh, 2001), which are negative reactions to a work stressor and can manifest as psychological (e.g., negative work attitudes) or behavioral (e.g., counter-productive behaviors) (Pindek et al, 2019). Particularly for industries impacted by work events, this process can lead employees to develop negative attitudes and behaviors toward their industry, such as industry turnover intentions, defined as an employee's willingness to leave an industry (Tongchaiprasit, & Ariyabuddhiphongs, 2016) and industry negative word-of-mouth, defined as the communication of personal experiences with an industry (Karabas, Joireman, & Kim, 2019). In other words, as a way to deal with the stress and negative emotions, employees might direct their emotions and behaviors toward leaving or staying in their industry.…”
Section: Conceptual Model and Hypotheses Developmentmentioning
confidence: 99%
“…Because most services are high in quality (Azar, 2009), it is critical to understand factors that may negatively affect the customer experience in such settings. To punish (Karabas et al , 2019; Voorhees et al , 2006) or to reward (Lynn, 2009, 2016) are both possible tipping motivations, and non-voluntary tipping encumbers both. As noted, the present results showed that, under high-quality service, non-voluntary tipping undermines the ability to reward one’s server, which interferes with positive emotions, translating into reduced return intentions.…”
Section: Discussionmentioning
confidence: 99%
“…“any service-related mishaps or problems (real and/or perceived) that occur during consumer’s experience with a firm” (Maxham, 2001, p. 11)]. Service failures (and failed recoveries) lead to perceived injustice (Goodwin and Ross, 1992), perceived negative motives (Joireman et al , 2013), desire for revenge (Karabas et al , 2019), anger (McColl-Kennedy et al , 2009; McColl-Kennedy et al , 2011), dissatisfaction (Maxham and Netemeyer, 2002; McCollough et al , 2000), negative word of mouth (Blodgett et al , 1997), switching (Bechwati and Morrin, 2003) and sabotage (Kähr et al , 2016). Research indicates such retaliatory behaviors aim to get even with the employees and the firm (Bechwati and Morrin, 2003).…”
Section: Empirical Review and Theoretical Developmentmentioning
confidence: 99%
See 2 more Smart Citations